Sub-cloning of Zinc Transporter Gene for Genetic Transformation to Improve Zinc Nutrient Status in Crop Plants - Mathapati, B. R.; Yamunarani, R.; Geetha, K. N.; Shankar, A. G. (International Journal of Bio-resource and Stress Management, 2015)
Nutrient deficiency stress is one of the major stresses limiting the crop productivity. Among the micronutrients, zinc deficiency is a widespread problem in plants as well as humans. In order to overcome zinc deficiency in human, the cost effective intervention would be to biofortify the food crops with zinc. While this approach heavily relies on the available knowledge of zinc homeostasis mechanisms in plants. Genetically modiﬁed plants developed by modulation of genes involved in zinc homeostasis, or genes inﬂuencing bioavailability, have shown promising results. Hence an attempt was made to sub-clone OsZIP1 zinc transporter gene of rice (Oryza sativa), so that the trans-gene construct could be subsequently used for genetic transformation of crop plants to accumulate more zinc. OsZIP1 is a high affinity zinc transporter gene, known to be overexpressed under zinc deprived conditions. Thus incorporation of this gene in crop plants would allow the plants to accumulate zinc even under zinc deficient conditions. In the absence of genetic variability in the crop plants for zinc content, which would limit breeding for zinc rich crops, transgenic development would provide a better alternative.